Competition for public transport services : Institutional framework and empirical evidence of bus services in Germany - Beck, Arne (Contributions to Economics, 2012)
This book evaluates the successes, failures, and factors that influence the competition for public bus transport services. Using Germany as a case study, the author explains the dichotomous system of a market with licenses for commercial services, where operators are granted exclusivity, and licenses for non-commercial services, where supplementary direct subsidies are tendered out by public transport authorities. The empirical analysis is based on primary data usually not publicly available, and supplemented by numerous expert interviews. The book aims to provide a basic understanding of the players and their options, offer insights into the German model, and make policy recommendations for those whose goal is to increase competition.